Electrical and thermal failure modes of 600 V p-gate GaN HEMTs. (September 2017) - Oeder, Thorsten; Castellazzi, Alberto; Pfost, Martin
Abstract: A study of electrical and thermal failure modes of 600 V p-doped GaN HEMTs is presented, which focuses on the investigation of short-circuit limitations. The electrical failure mode seems to be an electrical field breakdown in the structure which is caused by excessive carrier concentration, rather than primary thermal generated. Accordingly, a thermal failure mode is observed, which features a distinctive behaviour and seems to be similar to schottky-gate HEMTs. Concerning the electrical failure mode, a specific p-gate HEMT short-circuit safe operating area (SCSOA) is presented as a novelty. However, a short-circuit capability of up to 520 V can be achieved, regarding the design of the gate-drive circuit. Highlights: A study of electrical and thermal failure modes for GaN HEMTs is presented, which focuses short-circuit limitations. A distinctive behaviour of the electrical and the thermal failure mode is observed. A strong dependence of the short-circuit withstand capability is observed, regarding to the design of the gate-drive circuit. A specific p-gate HEMT short-circuit safe operating area (SCSOA) is presented as a novelty.